Pilgrimer, turister och mångfaldens organisation: Reflektioner kring en essä av Zygmunt Bauman - Ronström, Owe (Kulturella Perspektiv – Svensk etnologisk tidskrift, 1995)
Taking as its point of departure an essay by sociologist Zygmunt Bauman, the present article discusses some aspects of the organization of cultural and social diversity in contemporary Sweden. One of the most central projects of modernity has been the search for identity. Among the metaphors used to describe the identity-seeking personality engendered by modern society is that of the pilgrim. The strategy of the pilgrim was deferred gratification, and his goal to systematically mould the world into a desired shape. Such a project presupposed a constant, formable world. However, in a postmodern society, the rules of the game have been changed and continue to change all the time. Out of this impermanent condition emerge new life strategies (eg. those of the flaneur, the vagabond, the tourist, the player), based upon fragmentary, non-continual relationships. Individuals are temporarily united in groups bearing distinct characteristics and struggling for visibility with one another, to create increased social, cultural and political room. In this struggle, aesthetic, expressive forms stressing sensuality, play and desire are placed in the foreground, forms dedicated to creating and maintaining cultural identity as well as communicating them. The result of this can be that that which is thereby dramatized acquires the character of something faked and inauthentic, lacking serious intention. The author claims that it is necessary to discover new ways of describing and explaining this serious game through the ways in which it acts toward the world, using forms, expressions and meanings which perhaps more than anything else characterize mankind’s relationship with its surrounding.